PERANCANGAN TELEVISION COMMERICAL (TVC) UNTUK WORKSHOP DETAILING BRO DENGAN TARGET PASAR PEMILIKI MOBIL USIA 24-30 TAHUN DI KOTA MALANG - Davindra Kayana Zada Wahyudi; Aditya Nirwana; Ayyub Anshari Sukmaraga (Ma Chung Press, Universitas Ma Chung, 2026)
Car detailing services have seen rapid growth in major cities across Indonesia, including Malang. However, public awareness regarding the aesthetic benefits and importance of detailing as a part of vehicle maintenance remains relatively low. Detailing Bro, a professional car detailing service based in Malang, continues to face challenges in its promotional efforts. Therefore, the objective of this design project is to develop a promotional medium in the form of a television commercial (TVC), targeting car owners aged 24–30 years in the city of Malang. This project employs a qualitative research method, consisting of literature studies, interviews, field observations, and visual documentation. The TVC is designed using a storytelling approach that integrates both educational and promotional elements, delivered through a dynamic and narrative visual style tailored to the characteristics of the target segment. The concept emphasizes vehicle aesthetics, the importance of routine maintenance, and the ease of understanding the car detailing process. The outcome of this project is a TVC presented in two versions: the first with a duration of 1 minute and 5 seconds, and the second with a 30-second runtime. Both outputs are composed as cinematic videos, featuring close-up visuals, fast-paced transitions, and strong, concise narration. In addition to the main output, this project also includes supporting promotional materials such as a diorama, tooned mini-scale models, a desk mat, and posters. These outputs are intended to serve as effective and relevant promotional tools for Detailing Bro while also enhancing public understanding of car detailing services.